Correlation between Radiological Liver Surface Nodularity and Intraoperative Findings in Cirrhotic Patients Undergoing Liver Surgery - ALI, RABIAA MAHMOOD; ATIQ, MUHAMMAD; BODLA, MARIA AFZAL; HASSAN, MUHAMMAD HABIB; SHERWANI, UMAIR KHAN; MAHMOOD, SIDRAH (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Precision in preoperative liver morphology assessment in patients with cirrhosis is necessary to plan surgical procedures and risk profile. Nodularity of the liver surface (LSN) seen on cross-sectional imaging is a structural distortion caused by fibrosis and regenerative nodules, and may offer a non-invasive surrogate with regard to the appearance of the liver surface intraoperative. Objective: The purpose of the study is to determine the relationship between the radiological surface nodularity of the liver and the findings of the liver surface during the surgery performed on the patient with cirrhosis in a tertiary care center. Methods: It was a prospective observational study that involved 100 patients with clinically and radiologically diagnosed liver cirrhosis who were planned to undergo elective liver surgery. Blinded radiologists reviewed preoperative contrast-enhanced CT and /or MRI within four weeks before surgery, and assessed nodularity of the liver surface on a semi-quantitative scale (grades 03). The hepatobiliary surgeons assessed the liver surface morphology intraoperatively independently in a similar grading system. Demographic, etiology of cirrhosis, laboratory parameters, and Child-Pugh class were noted. Radiological and intraoperative grading were the two variables analyzed by the level of Spearman rank correlation coefficient. Results: The authors found that the mean age of the study population was 52.4 years (10.8 years), and viral hepatitis was the most prevalent cause of cirrhosis. Most patients had moderate to severe nodularity on the surface of the liver as radiologically assessed. Similar distribution was found intraoperatively. The radiological liver surface nodularity and the intraoperative findings were strongly positively associated (Spearman r = 0.78, p = 0.001). Greater grades of radiological density were always correlated to more surface irregularity, hardness and evidence of portal hypertension that were found intraoperative. Conclusion: Radiological nodularity of the liver surface has a high correlation with intraoperative liver surface in cirrhotic cases. LSN, as a means of assessment of preoperative imaging, is a valid, non-invasive instrument that may help in the arrangement of the surgery and the evaluation of risks in patients undergoing liver surgery.